Activation of Serum Thrombotic Accelerator (STA) by Digitonin and Saponin - Howell, R. M; Scott, G. B. D (Thrombosis and Haemostasis, 1967)
The steroid saponins digitonin and saponin white, compounds effective in disrupting membrane lipid-protein, have been shown to activate STA precursor.Ultracentrifuge studies showed a radical alteration in the floatation behaviour of the precursor complex on activation by digitonin, indicating an increase in its molecular size.Gel-filtration studies, on the other hand, revealed that activation by digitonin was reversible, since passage down a Sephadex G-200 column not only removed digitonin but abolished all activity, the latter being fully restored by the further addition of digitonin. Furthermore, since the elution positions of inactive precursor and deactivated STA were identical, this de-activation was accompanied by the return of the complex to its original size. The failure of cardiac glycosides, other than digitonin, to activate the precursor may be due to their being more hydrophobic and suggests that hypercoagulability leading to possible thrombosis does not arise from their therapeutic use.